UJI SINERGIS KONSORSIA BAKTERI INDIGEN LCN DENGAN KONSORSIA BAKTERI TANAH DI KEBUN PERCOBAAN UNIVERSITAS MUHAMMADIYAH METRO SEBAGAI SUMBER BELAJAR BIOLOGI - Rifai, M Rustam -; widowati, Hening; sutanto, *Agus (Universitas Muhammadiyah Metro, 2020)
Abstract: Antagonistic bacteria in the activities of one organism with other organisms compete with each other in fighting over places, air, water, food (nutrients). If the bacteria do not compete with each other but those bacteria can interact and synergize, and share the same nutritional sources and behave cooperatively between bacteria in their habitat. It is said to be synergisticThe goal is to find out the 15 consortia of LCN indigenous bacteria with soil bacteria can be synergistic so, it can be consortified. To utilize the synergistic test results of the consortia of LCN indigen bacteria with soil bacteria as a source of learning biology. The research design is a quantitative experiment . Synergistic test using Streak Plate Method on Nutrient Agar medium. The test results show that X2value 56.86> X2table 23.68 with α 0.05 in the chi-square table, so it can be concluded that there is a synergy between LCN Indigenous Bacteria and Soil Bacteria. The validation results show that the microbiology practicum guide with 96% results has a very good qualification so, it is suitable as a biology learning source in the form of a microbiology practicum guide based on scientific approach.